2017
DOI: 10.7150/jca.19197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 7th Edition of AJCC Staging System for Nasopharyngeal Carcinoma

Abstract: Purpose: To evaluate and improve the 7th edition International Union against Cancer/American Joint Committee on Cancer staging system for nasopharyngeal carcinoma.Methods: A retrospective review of the data from 905 patients with biopsy-proven non-disseminated nasopharyngeal carcinoma was performed. All the patients were examined by magnetic resonance imaging (MRI) and received radiotherapy.Results: Satisfied distributions among the stages were observed in the 7th edition staging systems. LRFS only differed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…20 Fourth, imaging examination in the IMRT era is superior to that of the past, an improvement which facilitates better treatment. We also observed that T and N stage and age were independent predictors for OS in the multivariate Cox proportional hazards model analysis, which was consistent with previous studies [21][22][23] and which demonstrated the rationality of the staging system based on imaging guidance in the IMRT age. The present study showed that LRFS was correlated with T stage, and the LRFS of T1-2 cases was significantly higher than that of T3-4 cases in the multivariate analysis (HR=4.51, 95% CI: 1.33-15.1, P=0.017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…20 Fourth, imaging examination in the IMRT era is superior to that of the past, an improvement which facilitates better treatment. We also observed that T and N stage and age were independent predictors for OS in the multivariate Cox proportional hazards model analysis, which was consistent with previous studies [21][22][23] and which demonstrated the rationality of the staging system based on imaging guidance in the IMRT age. The present study showed that LRFS was correlated with T stage, and the LRFS of T1-2 cases was significantly higher than that of T3-4 cases in the multivariate analysis (HR=4.51, 95% CI: 1.33-15.1, P=0.017).…”
Section: Discussionsupporting
confidence: 91%
“…That finding was consistent with the latest research. 21,22,30 In general, acute and chronic toxicities were tolerable. Acute injuries grade 3 and above accounted for less than 30% of all toxicities, and those injuries improved after symptomatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The clinicopathological information of these patients is listed in Table I . The clinical stage was defined based on the International Union Against Cancer ( 24 ). All patients provided written informed consent for the use of clinical materials, and the current study was approved by the Institutional Ethics Committee at Jiangsu Taizhou People's Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the prognosis of patients with NPC is primarily based on the Tumor-Node-Metastasis (TNM) staging system. However, extreme variation in clinical outcomes has been reported among patients with the same TNM stage who received similar treatment regimens 4. This phenomenon suggests that the present staging system alone is far from a perfect predictive tool for prognosis and treatment efficacy.…”
Section: Introductionmentioning
confidence: 98%